SUBMODUL HAMPIR PRIMA ( ON ALMOST PRIME SUBMODULES ) - , DYANA PATTY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In modul theory, we define prime submodules which motivated by the definition of prime ideals in a ring R (i.e assumed that R be an R-module R). Let R be a commutative ring with identity and M be an R-module. A proper submodule N of M is called prime if whenever r 2 R